Parents’ Supports For Deaf Children - Sitaningrum, Cicilia Ayunda; Sinaga, Juster Donal (SOLUTION, 2020)
This research aims to describe 1) parents’ knowledge about their deaf children; 2) parents’ obstacles in dealing with their deaf children; 3) forms of parents’ supports for their deaf children; 4) a process of parents’ supports for their deaf children; 5) parties involved in giving supports for deaf children.This research was qualitative research with a case study approach. The research data source was a parent whose child is deaf in a private School for Exceptional Children (SLB) in Jakarta. The data collection technique was conducted through interviews. The data analysis techniques used were data collection, data reduction, data presentation, and data verification.  The research shows the following results. 1) Parents’ knowledge about their deaf children is children with hearing impairments speaking not fluently. Their knowledge increases when they take their children to an ENT specialist. Deaf children have different levels of severity, need hearing aid, and use minimal vocabularies. 2) Parents’ obstacles in dealing with their deaf children in which their children are difficult to communicate, be controlled during tantrum, and being often lazy to study or go to school. 3) Parents’ supports in the form of providing speaking training, giving love and enthusiasm, entrusting children to school dormitories to practice independence, giving rewards for their achievement, and involving children in competitions to develop their passions. 4) The process of parents’ supports for their deaf children is by trying to persuading their children when they are tired of studying or going to school and trying to meet all their children’s needs. 5) Parties involved in giving supports for deaf children are father, older siblings, and homeroom teachers